2021
DOI: 10.37478/mahajana.v2i2.952
|View full text |Cite
|
Sign up to set email alerts
|

Community Service in Study Potential Technology of Education Tour and Business Prospects of Traders in Tulungagung

Abstract: The purpose of this study is to identify the potential for educational tourism, training facility and business prospects that can be developed by street vendors in Tulungagung Regency, analyze the obstacles faced by each street vendor area, determine the potential for educational tourism and business prospects for street vendors in each area in Tulungagung district. The research location is in 5 street vendors in Tulungagung district. This type of research is descriptive, namely in-depth analysis of the data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…In contrast, in social life, it can be in the form of religious systems, social systems and organizations, knowledge systems, livelihood systems, and systems of technology and equipment. Even though it has local value, its value is considered universal (Hastuti & Setyawan, 2021). Field of research on cultural elements of ethnoscience in Tulungagung shown in Table 1.…”
Section: Local Wisdom Of Tulungagung and Implementation In Etnosciencementioning
confidence: 99%
“…In contrast, in social life, it can be in the form of religious systems, social systems and organizations, knowledge systems, livelihood systems, and systems of technology and equipment. Even though it has local value, its value is considered universal (Hastuti & Setyawan, 2021). Field of research on cultural elements of ethnoscience in Tulungagung shown in Table 1.…”
Section: Local Wisdom Of Tulungagung and Implementation In Etnosciencementioning
confidence: 99%
“…Kegiatan penyempurnaan dilakukan dengan penyuntingan dan perbaikan tulisan (revisi). Pembimbingan seperti ini dikemas oleh penulis dalam kegiatan PKM (Pengabdian Kepada Masyarakat) (Hastuti & Setyawan, 2021).…”
Section: Pendahuluanunclassified
“…In accordance with the fact that the family is a primary education environment where the child first gets an education that is from the family environment, so that the education provided by the family will be the foundation of the formation of the child's personality. This means that the education of the family obtained by the child will be the basic knowledge for the child in conducting the next education in both the school and the community (Hastuti and Setyawan, 2021).…”
Section: Introductionmentioning
confidence: 99%